Sniffin' Sticks Screening 12 Test can assist in the clinical distinction between psychiatric disorders and neurological/neurodegenerative disorders: Biomarkers (non‐neuroimaging) / Differential diagnosis. (7th December 2020) - Pachi, Ioanna; Evans, Andrew H; Loi, Samantha M; Eratne, Dhamidhu; Malpas, Charles B; Walterfang, Mark; Farrand, Sarah; Kelso, Wendy; Velakoulis, Dennis
Abstract: Background: Distinguishing primary psychiatric disorders (PPD) from neurological/neurodegenerative disorders (NND) is a common diagnostic dilemma in clinical practice. Numerous studies have focused on whether cognitive, neuroimaging or blood/ cerebrospinal fluid (CSF) are of assistance in this clinical scenario. Olfactory impairment has not however been systematically examined as a clinical tool for this purpose. The aim of this study was to identify whether performance in olfactory identification can distinguish NND and PPD. Method: This was a cross‐sectional retrospective study of inpatients assessed in Neuropsychiatry, Royal Melbourne Hospital (RMH) over the period 2015‐2019. Neuropsychiatry is a tertiary / quaternary service which provides diagnostic work up for patients with cognitive, psychiatric and neurological symptoms. Data extracted from the admission records included: demographics, tobacco use, medical comorbidities, cognitive function using the Neuropsychiatry Unit Cognitive Assessment Tool (NUCOG), and odour identification assessed using the Sniffin' Sticks Screening 12 Test (SS12). The final discharge diagnosis for all patients was informed by established diagnostic criteria. Result: 121 patients were identified who had valid Sniffin Stick testing over this period. 88 patients (72.7%) were diagnosed with NND (mean age‐ 60, including Alzheimer's dementia, frontotemporal dementia, Lewy body parkinsonian‐related dementias [Parkinson's disease, Multiple Systematic Atrophy, Dementia with Lewy bodies] and other neurological causes of dementia), 33 patients (27.3%) were diagnosed with PPD (mean age=57 years, including mood and psychotic disorders). Patients who scored ≤8 in SS12 were more likely to have NND than PPD, even after adjustment for age, gender and tobacco use [(p=0.005, unadjusted OR=3.51, 95% CI=1.463, 8.410), (p=0.009, adjusted OR=3.848, 95% CI=1.395, 10.617)]. Receiver Operating Curve (ROC) analyses demonstrated that a score of ≤8 differentiated NND from PSY with sensitivity of 56.8% and specificity of 72.7% (ROC area under the curve of 0.672, p=0.004). Conclusion: Patients presenting with diagnostically complex neurocognitive / neuropsychiatric difficulties who score 8 or less on Sniffin' Sticks are more likely to have a neurodegenerative illness. A cut‐off score of 8 is potentially a "red‐flag" for clinicians faced with the diagnostic question of PPD versus NND.